2018
DOI: 10.1371/journal.pone.0207890
|View full text |Cite
|
Sign up to set email alerts
|

AGMT3-D: A software for 3-D landmarks-based geometric morphometric shape analysis of archaeological artifacts

Abstract: We present here a newly developed software package named Artifact GeoMorph Toolbox 3-D (AGMT3-D). It is intended to provide archaeologists with a simple and easy-to-use tool for performing 3-D landmarks-based geometric morphometric shape analysis on 3-D digital models of archaeological artifacts. It requires no prior knowledge of programming or proficiency in statistics. AGMT3-D consists of a data-acquisition procedure for automatically positioning 3-D models in space and fitting them with grids of 3-D semi-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 48 publications
0
34
0
1
Order By: Relevance
“…All models are available for scienti c and academic purposes at ZENODO (35). The 3D models were processed using the AGMT3-D software (36,37). This consists of a data-acquisition procedure for automatically positioning 3D models in space and tting them with grids of 3D semi-landmarks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All models are available for scienti c and academic purposes at ZENODO (35). The 3D models were processed using the AGMT3-D software (36,37). This consists of a data-acquisition procedure for automatically positioning 3D models in space and tting them with grids of 3D semi-landmarks.…”
Section: Methodsmentioning
confidence: 99%
“…A speci c morphometric analysis of handaxe symmetry in strata a and c (32) has shown that human groups mastered tool symmetry from 700 ka onwards, despite lower shaping intensity at that time. In order to continue to track the technological drift between ca 700 and ca 450 ka, we applied the WEAP method (34) on the whole corpus of handaxes of this site, combining for the rst time a technological analysis with a broader morphometric approach using AGMT3-D software (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been developed in the last years, and successfully used in the analysis of bifacial tools in a growing number of case studies [ 62 , 98 – 100 ]. Shape statistical analysis were carried out with the software AGMT-3D, which has the advantage of performing several steps automatically [ 101 ]. Files of the objects in Wrl-format were imported into the software and at first processed for the acquisition of data: after a general alignment as described above, 3D semi-landmarks were obtained automatically with the construction of a grid formed by 50 meridians and 50 parallels, for a total of 2,500 landmarks on each surface.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In general, the morphological variability of scrapers and backed flake tools is higher than that of Keilmesser, respectively of about 12% and 18% (Table 9); this value is measured as the mean multidimensional Euclidean distance of the items in the group from the group's centroid (i.e. mean shape): the higher the value, the higher the variability [101].…”
Section: D Morphological Datamentioning
confidence: 99%
“…The digitization of information allows a faster, more efficient and standardized recording of data that facilitates the synthesis work required by the discipline. Many database programs are developing in archaeology (Herzlinger & Grosman, 2018;LeFebvre et al, 2019) and physical anthropology, either at the initiative of personal development or collaborative (Eve & Hunt, 2008;Feugère, 2011;Gailledrat, 2016), or still institutional (Cuy et al, 2017;Meghini et al, 2017). At the same time, targeted tools are also being developed to meet specific needs: sex determination (Brŭžek et al, 2017), stature calculation (Chan, 2013), construction of stratigraphic diagrams (Desachy, 2008) or for 3D visualizations of skeletons (Kepple et al, 1998;Proko, 2014;Sachau-Carcel, 2012).…”
Section: Introductionmentioning
confidence: 99%